Polymorphism of magnesium metasilicate and its role in the production of nonaging steatite ceramics; Glass and Ceramics; Vol. 54, N 11-12 - Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (1997, 1997)
As established by a DTA and high-temperature x-ray diffractometric study, the phase transition of high-temperature protoenstatite to clinoenstatite on cooling is related to the crystal size. Methods are proposed whereby it is possible to make thermally stable, nonaging steatite ceramics with the protoenstatite crystallized into extremely fine grains. In this way, nonaging steatite ceramics of improved service properties can be produced